Femoral artery blood flow and its relationship to spontaneous fluctuations in rhythmic thigh muscle workload - Osada, Takuya; Rådegran, Göran (Clinical physiology and functional imaging, 2009)
Summary Background and aim:  Limb femoral arterial blood flow (LBF) is known to increase linearly with increasing workload under steady‐state conditions, suggesting a close link between LBF and metabolic activity. We, however, hypothesized that sudden physiological and spontaneous changes in exercise rhythm, and consequently workload temporarily alter blood flow to the working muscle. LBF and its relation to fluctuations in the contraction rhythm and workload were therefore investigated. Methods:  LBF, measured by Doppler ultrasound, and the achieved workload, were continuously measured in nine subjects, aiming to perform steady‐state, one‐legged, dynamic knee‐extensor exercise at 30 and 60 contractions per minute (cpm), at incremental target workloads of 10, 20, 30 and 40 W. Results:  In agreement with previous findings, LBF increased positively and linearly (P<0·05) with increasing target workload. However, LBF was inversely and linearly related (P<0·05) to the actually achieved workload, when measured over 60 consecutive contraction–relaxation cycle bouts, for each target intensity at 30 and 60 cpm respectively. Thus any sudden spontaneous increase or decrease in the achieved workload transiently altered the relationship between LBF and the achieved workload. The influence upon the magnitude of LBF, due to fluctuations in the achieved workload from the target workload, was furthermore similar between target workload sessions at 30 and 60 cpm respectively. LBF was, however, not associated with variations in the contraction frequencies. Conclusions:  These findings indicate that a transient sudden increase in the workload more rapidly impedes LBF and that vasodilatation may be elicited to restore the intensity related steady‐state LBF response in relation to the average metabolic activity.